قياس و تحليل تكلفة الفساد الإداري والمالي : دراسة تطبيقية في جامعة صلاح الدين/عمادة كلية شؤون الطلبة - غازي عثمان محمود (PROSPECTIVE RESEARCHES, 2023)
The phenomenon of corruption is a sensitive subject that most of the developed and developing countries suffer from. Therefore, many governments worldwide including Kurdistan Region Government have conducted intensive campaigns to put an end to this phenomenon. Hence, this paper aimes at measuring the administrative and financed corruption costs and analyzing the factors behind this phenomenon and supporting the effort of those who care about it. It is worth mentioning that the following speech by the president Barzani was a motivating stimulus to write this paper. 'Kurdistan will not protect anyone involved in corruption'.